Weaknesses of 'wage-led growth'*. (July 2017) - Skott, Peter
Abstract : The emphasis in post-Keynesian macroeconomics on wage- versus profit-led growth may not have been helpful. The profit share is not an exogenous variable, and the correlations between the profit share and economic growth can be positive for some exogenous shocks but negative for others. The terminology, second, suggests a unidirectional causality from distribution to aggregate demand while in fact distribution can itself be directly affected by shifts in aggregate demand. The reduced form correlations, third, depend on interactions with the labor market, and a focus on the goods market can be misleading. If, fourth, empirical estimates are taken at face value, the support for wage-led conclusions is much weaker than suggested by the literature. A focus on the growth benefits of a reduction in inequality, finally, makes for an impoverished policy discussion.